Agronomic and productive characteristics of three varieties of alfalfa (Medicago sativa L.) in the central highlands of Peru - Vilcara Cárdenas, Edgardo Arturo (2023)
In the Andean region, livestock is sustained by feeding on natural pastures, the same ones that depend on rain for their growth and production. Its poor quality and low yield have a negative effect on the productive indices of cattle. An alternative to this problem is the introduction of improved and permanent pastures of good nutritional value and higher yield, which is why the present work was carried out with the objective of evaluating the agronomic and productive characteristics of three varieties of alfalfa, in the central highlands, in order to select the one with the best performance. The experimental area was 198 m2 (11 m x 18 m) where 96 m2 of alfalfa were established corresponding to three plots of 32 m2 each (4m x 8 m) separated by 1.5 m. The completely randomized experimental design was used with 3 treatments (varieties WL350, WL450 and Hortus401) and 8 repetitions. The variables evaluated were: plant height (AP), fresh green fodder yield (FV) and dry matter (MS) and growth rate (TC). WL350, WL450 and Hortus 401 reached heights of 30.25; 32.75 and 23.50 cm and dry matter of 2 258; 2 714 and 1 813 kg ha-1 corte-1, respectively (p<0.05). The WL450 variety showed a higher growth rate (22.31 kg DM ha-1 day-1) compared to the other two varieties.  It is concluded that the three varieties had good productive performance of forage. WL 450 was the best performing alfalfa variety for the evaluation site conditions.